Self-awareness as the key to successful adherence to antiretroviral therapy among people living with HIV in Indonesia: A grounded theory study - Sri Yona; Chiyar Edison; Astuti Yuni Nursasi; Rita Ismail (Belitung Raya Foundation, Indonesia, 2023)
Background: Adherence to antiretroviral therapy (ART) continues to pose a significant challenge for people living with HIV (PLWH). Non-adherence to ART can have far-reaching implications for patient well-being, particularly in increasing the risk of opportunistic infections when medication is not taken as prescribed. Objective: This study aimed to develop a theoretical model that explains how PLWH in Indonesia adhere to their ART regimen and the strategies they follow to maintain adherence. Methods: The study used a grounded theory approach. Data were collected through face-to-face in-depth interviews with 21 PLWH who had been taking ART for six months or more at a non-governmental organization (NGO) in Jakarta, Indonesia, between July 2019 and November 2019. Theoretical sampling was used, and the data analysis method of Corbin and Strauss was utilized, including open coding, axis coding, and selective coding. Results: Three stages were identified as a process of adherence to the ART regimen: 1) initiating ART, 2) missing the connection, and 3) taking control. Self-awareness was identified as the central core theme describing the ART adherence process. Conclusion: Having adequate self-awareness to take ART regularly is crucial to improving adherence to ART. Moreover, social support from one’s spouse and family members can help patients maintain adherence. Therefore, self-awareness and support systems should be included as components in nursing interventions when starting ART therapy. In addition, nurses can help identify potential support persons and provide information related to ART therapy.